Trillions for Military Technology How the Pentagon Innovates and Why It Costs So Much - Alic, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
Trillions for Military Technology explains why the weapons purchased by the U.S. Department of Defense cost so much, why it takes decades to get them into production even as innovation in the civilian economy becomes ever more frenetic, and why some of those weapons don't work very well despite expenditures of many billions of dollars. It also explains what do about these problems. The author argues that the internal politics of the armed services make weapons acquisition almost unmanageable. Solutions require empowering civilian officials and reforms that will bring choice of weapons "into the sunshine" of public debate.
Keywords: Military history; Business enterprises—Finance.; America—History.; Economic history; History of Military; Business Finance; History of the Americas; Economic History